Análisis de los productos comunicacionales que se genera en el municipio de Loja acerca del proyecto de gestión integral en manejo de residuos sólidos para la educación ambiental del cantón, periodo junio – octubre de 2019 - Villamagua Vicente, Michelle Katherine (2020)
The present research work was carried out in order to analyze the communicational products that the Municipality of Loja manages regarding the Project of Integral Management in Solid Waste Management for the environmental education of the canton. The scientific method was used with the aim of obtaining a high knowledge of the subject. The research is descriptive in nature with a quantitative-qualitative approach, since techniques such as the interview, survey and observation cards were applied, which served to understand the management of internal and external communication of the institution. The surveys were applied to a sample of citizens from the urban sector. The interviews were aimed at the following people, Mr. Solimán Salinas in charge of project communication during the month of June, Engineer José Merecí Coordinator of the Management Center and Magister María Alejandra Luzuriaga Vasquez Director of the Department of Communication. This technique was also carried out by the environmental communication specialist and teacher Hever Sánchez in order to contrast the information. The observation sheets were used to analyze the communication products issued by the Municipality of Loja, during the period June-October 2019. With the data obtained, the analysis was carried out, according to the results it is concluded that most of the citizens are unaware of the Comprehensive Management Project in Solid Waste Management. Likewise, it was observed that there is poor communication and disorganization in the departments in charge of managing project information, since there are few communicational products and innovative communication strategies. Currently, it is very difficult to reach citizens only through a channel of dissemination, which is why the research carried out in the Municipality of Loja suggests the need to search for new strategies in the development and dissemination of communicational products that allow improving the performance of the Comprehensive Management Project in Solid Waste Management for environmental education in the Loja canton.